Le street art entre valorisation informelle du territoire et logiques d’institutionnalisation - Aude Le Gallou (EchoGéo)
Drawing on an analysis of the Saint-Nazaire based project, Les Oides, this paper aims to address geographical and political issues related to the urban valorization of street art. It first argues that the artistic project can trigger evolutions of city users’ representations and practices without being subject to any institutional recognition. The paper then focuses on the logic of the project’s legitimization and shows that institutional valorization faces difficulties even though the project seems to be consensual. It eventually outlines the gap between street art’s ability to valorize urban space on the one hand and political choices that leads to official recognition of this potential.